CORPORATE GOVERNANCE AND AUDIT REPORT LAG IN NIGERIA (Journal of Global Accounting, 2023)
This study has been carried out to investigate corporate governance and audit report lag in Nigeria. The study used ex-post factor research design. The population of the study consist of eight (8) quoted oil and gas companies on the Nigerian Exchange Group (NEG) as at 31st December 2022. Out of the eight listed oil and gas companies 7 were used as sample size due to availability of data using the purposive sampling technique. The study period is from 2012-2021. The data were collected from the annual reports and accounts of the seven (7) sampled quoted oil and gas companies on the Nigerian Exchange Group (NEG) and were analyzed using the descriptive and inferential statistics and the hypothesis were tested using panel corrected Standard Error. The results show that board of directors has positive and insignificant effect on audit report lag while audit committee size has positive and significant effect on audit report lag. We concluded that the size of the audit committee has a significant role to play in achieving early audit report lag. The study recommended that a good size and experienced individual should be   encouraged to achieve a better audit report lag.
Keywords: Audit Report Lag; Corporate Governance; Nigerian Exchange Group (NEG); Oil & Gas Companies